Luther's 1521 Magnificat Commentary - Kreitzer, Beth (Lutheran quarterly, 2021)
By the end of 1520, Luther was a publishing sensation. By this stage of his life Luther was confident that the gospel would triumph. He had churned out major works such as the Treatise on Good Works, Address to the Christian Nobility, Babylonian Captivity of the Church, and The Freedom of a Christian. Facing the bull of excommunication, Luther turned his attention to Mary's Magnificat (Lk 1:46b-55), which provided him the opportunity to tackle several important topics and to provide pastoral guidance to ordinary Christians. Despite its prominence in the life of the church, according to Luther, the Magnificat was little understood by most Christians, especially by those in powerful positions. Luther's comments focused on the heart of the song, encouraging his own elector, John Frederick, as well as other rulers, to remember that God is the giver of all good gifts, including political office, and to be mindful as well that God can take away what he has given.